(untitled) (Research, Society and Development, 2023)
The objective was to analyze the epidemiological situation of congenital syphilis in a state in the Western Amazon. This is a cross-sectional study, with a quantitative approach, sectional type, with secondary data collected at the Information Department of the Unified Health System - DATASUS, tabulated from the TABNET. Data were analyzed using descriptive and inferential statistics in order to verify the associations between the variables of interest. The behavior of the disease in the state shows an oscillating trend, where most cases occurred in 2018 (96), showing a downward trend in 2021 with the notification of (47) cases. There was a general incidence of 4.8 cases per thousand live births, above the target set by the Pan American Health Organization. Most newborns diagnosed with the disease were in the age group of up to 6 days of life 365 (96%), female 192 (50%), race/skin color brown 325 (85%), whose mothers had incomplete primary education 118 (31%). Most mothers performed prenatal care 322 (85%), whose diagnosis of maternal syphilis occurred at the time of delivery/curettage 168 (44%), and most of their sexual partners were not treated 285 (75%). Most newborns were classified as recent congenital syphilis 357 (94%), progressing mostly to live children 331 (87%). The disease is a public health problem in the region studied and it is suggested that it is associated with failures in prenatal care related to timely diagnosis and treatment of partners.